Urban Enviromvrental Health In Developing Countries: A Case Study Of Penang Island, Malaysia - Abdullah, Jamalunlaili (1997)
Environmental issues are rapidly gaining prominence in the field of city and regional planning. As experts and authorities acknowledge the linkage between the rate of growth in global urbanization, and deterioration in the quality of the environment, environmental planning is receiving increasing attention in urban planning and development projects worldwide.